Suctional Losses in a Two-Rotor Vacuum Pump with External Compression - Raykov, A. A.; Burmistrov, A. V.; Salikeev, S. I. (Russian engineering research, 2024)
The losses of productivity observed in gas suction within an oil-free two-rotor vacuum pump are considered. In CFD (computational fluid dynamics) modeling of pump operation, both with and without a pressure difference, the influence of heating and throttling of the gas is analyzed, as it passes through the intake tube and as it fills an isolated chamber. Experimental data confirm the modeling results. Gas heating in suction has the greatest influence on pump performance. The proposed formula determines the losses with no more than 6% error.